A New Approach to Assessing the Science Contribution to the State Economy - Belov, Alexandr; Svistun, Lyudmyla; Glushko, Ðlina (International Journal of Engineering and Technology, 2018)
The article is dedicated to the issues of assessing the science contribution to the state economy. The suggested authorâ€™s approach to estimation the science impact on the economic growth. The authors carried out modeling of estimation the role of science in the countryâ€™s economic development on the example of Great Britain. According to the models obtained, the volume of R&D expenditures has the most significant influence on the country's economic development, and in the long outlook this impact is almost twice as high as in the short-term one. The article conclusion contains advantages and limitations of authorâ€™s approach to assessing the science contribution to the state economy.Â Â